A bionic robotic ankle driven by the multiple pneumatic muscle actuators - Delei Fang; Fangyuan Ren; Jianwei Wang; Pan Li; Lin Cao; Junxia Zhang (Biomimetic Intelligence and Robotics)
The traditional pneumatic muscle robot joint has weak load capacity and low control precision. This paper proposes a bionic robotic ankle driven by multiple pneumatic muscle actuators. The structural design of the bionic robotic ankle and the drive mechanism that imitates human muscle recruitment are introduced. A dynamic model of the ankle and a static model of the pneumatic muscle actuator are established to analyze the driving characteristics. The multi-muscle recruiting strategy and load matching control method are optimized, and the output characteristics are simulated, including the robotic ankle driven by a single pneumatic muscle actuator, the robotic ankle driven by dual pneumatic muscle actuators, and the bionic ankle driven by multiple pneumatic muscle actuators. A prototype and testing platform are developed, and experimental research is carried out to validate the theoretical analysis and simulation. The results show that the bionic robotic ankle driven by multiple pneumatic muscle actuators can match varied loads, effectively reducing angle error and increasing output force.